2018
DOI: 10.1007/s11199-017-0882-4
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Judgments about the Desirability of Toys for Their Children: Associations with Gender Role Attitudes, Gender-typing of Toys, and Demographics

Abstract: Parental toy selection and responses to toy play are important factors in children’s gender socialization. Reinforcing play with same-gender-typed toys guides children’s activities and limits their action repertoires in accordance with gender stereotypes. A survey of 324 Austrian parents of three- to six-year-old children was conducted to investigate parents’ judgments about the desirability of different types of toys for their children and how these judgements relate to parents’ gender-typing of toys, gender … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
58
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 57 publications
9
58
1
5
Order By: Relevance
“…Previous work has argued that it is important and valuable to show both women and men as capable of expressing both masculine and feminine characteristics (Bem 1975), and the positive implications for children's gender identity development, and associated psychosocial outcomes, are clear (Martin et al 2016). However, the higher proportion of feminine behavior by prince characters is certainly no reflection of any obvious role change for men and young boys in society, or greater acceptance of men's feminine interests, as numerous studies suggest they are still consistently and firmly guided away from such pursuits (e.g., playing with feminine toys, see Kollmayer et al 2018). The reasons behind more feminine behavior in princes are therefore unclear.…”
Section: The Changing Princementioning
confidence: 99%
“…Previous work has argued that it is important and valuable to show both women and men as capable of expressing both masculine and feminine characteristics (Bem 1975), and the positive implications for children's gender identity development, and associated psychosocial outcomes, are clear (Martin et al 2016). However, the higher proportion of feminine behavior by prince characters is certainly no reflection of any obvious role change for men and young boys in society, or greater acceptance of men's feminine interests, as numerous studies suggest they are still consistently and firmly guided away from such pursuits (e.g., playing with feminine toys, see Kollmayer et al 2018). The reasons behind more feminine behavior in princes are therefore unclear.…”
Section: The Changing Princementioning
confidence: 99%
“…There may be differences between male and female caretakers on their attitudes to toys and gender. We leave these potential factors for future research, but encourage greater diversity in children's toy play to promote a reduction in gender stereotypes (Dinella & Weisgram, 2018;Joel et al, 2015;Kollmayer et al, 2018;Spinner, Cameron, & Calogero, 2018).…”
Section: Parental Attitude and Familiaritymentioning
confidence: 99%
“…An alternative interpretation would be that parents may be selecting toys according to their perceptions of the infants' pre-existing preferences. Parents rate gender-congruent and gender-neutral toys as more desirable than gender-incongruent toys for their children aged 3-6 years (Kollmayer, Schultes, Schober, Hodosi, & Spiel, 2018). A recent online survey was conducted by Weisgram and Bruun (2018) in which 238 prospective and 96 current parents' preferences on gender-specific toy purchases were measured.…”
Section: Introductionmentioning
confidence: 99%
“…The girls' toys were heavily based on traditional 'gender-roles' of the female as a care-giver concerned by appearances and portrayed as a passive character; whereas the boys' toys were based on construction and perceived the male as an 'active' character who gains merit through strength and bravery (Dinella, Weisgram, & Fulcher, 2017;Francis, 2010). Toys were found to give gender suitability cues via their colour, logos and functions which indicate whether they are more communal based, for girls; or agentic based, for boys (Kollmayer, Schultes, Schober, Hodosi, & Spiel, 2018;Wood, Desmarais, & Gugula, 2002). The differences in how the toys were aimed to accommodate for either gender highlight explicitly to the children different messages of how each child should behave and what attitudes were associated for either gender.…”
Section: What Reinforces Gender Stereotypesmentioning
confidence: 99%
“…Research found discrepancies in the findings of the parents' perceptions of gender and their actual attitudes and behaviour. For example, various literature found a common occurrence that parents tended to be more liberal and accepting in regard to the girls playing with toys aimed towards either gender than to towards the boys playing with toys aimed at either gender (Freeman 2007;Kollmayer et al, 2018;Our Watch, 2018;Wood, Desmarais & Gugula, 2002). Furthermore, Wood, Desmarais and Gugula (2002) highlight that parents often participate in gender stereotyped play with their children; however, parents are more gender flexible when they engage in play with girls.…”
Section: What Reinforces Gender Stereotypesmentioning
confidence: 99%